Paradoksalny azyl tożsamości – poszukiwanie tożsamości palestyńskiej w edukacji dwujęzycznej - Awida-Yehya , Nehaya (Studia Edukacyjne, 2020)
The research focuses on Arab parents who chose to send their children to the bilingual schools in Israel. The objective is to address the factors that led to the dropping out of Arab students from public education and their participation in alternative education. This research presents the problems of the Arab schools, both in terms of the quality of the instruction and the academic achievements. The main argument is that the goals of Arab education in Israel discuss the need to instill in the students the values of the State of Israel as a Jewish state, without referring to the fact that in this society there is an Arab minority with its own nationality and the right to be an integral part of this society. This ignoring of the needs of the Arab student caused a decline in the quality of the instruction and in the academic achievements of the Arab schools in Israel. As a result of the disappointment of the parents, especially the “intellectual” parents, in pedagogical and social terms and in terms of the students’ personal-national identity, “alternative education” developed in Arab society and Arab students dropped out of public education. This research found a high degree of satisfaction with alternative education in general and bilingual education in particular in all areas and primarily in the formation of the Arab student’s personal and national identity.